The Neo-liberal Twist of Law - Giordano, Valeria (Soft Power, 2024)
There is no doubt that the term law today is subject to transfigurations of its central constructs, originating from the processes of juridical globalisation that tend to falsify the self-referential and reassuring image of the Kesenian pyramid, revealing an extravagant contradictory pressure on the concept of law itself, which tends to correspond to a lexicon that is increasingly in trouble (Catania, 2008). Old languages and new concepts come out on a scenario populated by multiple and diverse actors in a fragmented and uneven set of normative production, increasingly detached from a legislative matrix, given the judicial and private vocation of global governance.